Improved diagnosis of reactivated toxoplasmosis. Issue 2 (April 1998) - Ashburn, D; Davidson, M M; Joss, A W; Pennington, T H; Ho-Yen, D O
Abstract : AIMS: To identify antigens detected by western blotting in primary Toxoplasma gondii infection and determine their role in diagnosis of reactivated toxoplasmosis. METHODS: Twenty three immunocompromised patients were tested by IgG western blotting. Patients were grouped retrospectively. Group 1 comprised 15 human immunodeficiency (HIV)/AIDS patients and included: group 1A (six patients with clinical and/or serological evidence of reactivation), group 1B (five patients with clinical evidence only), and group 1C (four asymptomatic patients). Group 2 comprised eight non-HIV/AIDS immunocompromised patients with clinical and/or serological evidence of reactivation. Immunocompetent patients (n = 23) with primary toxoplasmosis were a control group used to determine the progression of the antigens detected. RESULTS: In primary toxoplasmosis, antibodies against 6, 20, 22, 23, 25, 28, 29, and 36 kDa antigens predominated. Detection of four or more of the 6, 20, 22, 23, 25, and 36 kDa antigens was considered to be western blot positive. In two group 1A patients, western blotting indicated past infection. During reactivation, this reverted to being western blot positive. Three other group 1A patients were western blot positive. In three of five group 1B patients, western blot positive results improved serological diagnosis of reactivated toxoplasmosis (p < 0.05). In two of five group 1B patients and all four group 1C patients, western blot indicated past infection. In group 2, two of eight patients reverted from a pattern of past infection to western blot positive. Five other patients from group 2 were western blot positive. CONCLUSIONS: Detection of some low molecular weight antigens is diagnostic of reactivated toxoplasmosis. These antigens can be detected even with normal dye test titres and their detection improves the diagnosis of reactivated toxoplasmosis. They might be the result of the release of bradyzoites from ruptured tissue cysts.